Morphometry of fruit and seed of populations of Ferocactus pilosus from the Highlands of Tamaulipas - Rodríguez Ruíz, Erick Rubén; Vaquera Huerta, Humberto; Venegas Barrera, Crystian Sadiel; Cervantes Ortíz, Francisco; Poot-Poot, Wilberth Alfredo; Rangel Lucio, José Antonio (Revista Mexicana de Ciencias Agrícolas, 2023)
In Mexico, more than 75% of cactus species are subject to anthropogenic pressure and habitat destruction, as is the case of Ferocactus pilosus, so it is important to increase knowledge for their recovery in situ. The objective of the study was to determine how the semiarid environment of the Highlands of Tamaulipas tends to limit the distribution of five populations of F. pilosus and promotes morphological changes that operate in fruits and seeds. The dendrogram defined the similarity between populations II, III and IV of the barrel cactus, due to differences in stoniness and slight humidity condition due to the type of climate and elevation. The analyses Manova and Tukey demonstrated the existence of significant differences in seed number (SN) and seed weight (SW) of barrel cactus. The SN was statistically equal between populations II (674 ±191), III (657 ±221) and IV (643 ±246), while in the same populations, SW was 0.92 ±0.27, 0.9 ±0.3 and 0.88 ±0.34 mg, respectively. Populations II, III and IV of the Mexican fire barrel cacti took better advantage of the environmental conditions of the Highlands of Tamaulipas prevailing in 2013 and 2014, which caused a significant variation of SN and SW in the same populations of F. pilosus and the partial rejection of the hypothesis.
Keywords: barrel cactus; number of seeds; weight of seeds